Development of Wireless Patient’s Vital Sign Monitor Using Wireless LAN (IEEE.802.11.b/g) Protocol - Achmad Rizal; Vera Suryani; Jondri Jondri; Sugondo Hadiyoso (Institute of Advanced Engineering and Science, 2014)
Vital sign monitor is typical medical instrument for basic physiological measurement. Medical practitioner assesses a patient’s health condition by observing measurement results shown in display. In this research, we designed low cost, wireless, PC-based vital sign monitor. Signals captured in designed vital sign monitor are electrocardiogram (ECG), photoplethysmogram (PPG), and body temperature. Captured data are transmitted via wireless LAN module so that medical practitioner is able to monitor patient’s condition remotely from another room or place. The system worked well for maximum transmission distance about 45 meters for LOS condition and 20 meter for NLOS condition.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6429